Microwave drying kinetics and quality characteristics of corn - G, Song; Choudhary, Ruplal; Watson, Dennis G. (International Journal of Agricultural and Biological Engineering, 2013)
In recent years, microwave (MW) drying has gained popularity as an alternative drying method for a wide variety of food and agricultural products because of increasing concerns over product quality and production costs. However, the determination of drying kinetics that accurately describes microwave drying characteristics is crucial for the optimization of operating parameters, performance improvement of the drying system and product quality. The objective of this study was to investigate the drying kinetics and the quality characteristics of corn kernels, especially the effects of different initial moisture contents (18.3%, 26.3%, 34.3% and 42.3% db), MW power levels (70, 175 and 245 W) and exposure time (80 s and 120 s) on the drying kinetics, drying rate and various key quality parameters. The results indicated that the increased drying rate at higher power levels (P3, 245 W) reduced the drying time considerably but increased stress crack index and reduced germination. In addition, it reduced bulk density, true density and thousand grain weight (TGW). The germination rate of corn was the highest at MW power level P1 (70 W), with the lowest drying rate and observed to decrease with increase in initial moisture content. The reduction in exposure time decreased stress crack index and increased germination rate, bulk density and true density. The correlation analysis among drying rate, germination, stress-crack index (SCI), bulk density, true density and TGW showed that increasing drying rate could lead to an increase in SCI and decrease in germination, bulk density and true density.